2020
DOI: 10.17159/2309-8309/2020/v19n1a4
|View full text |Cite
|
Sign up to set email alerts
|

The accuracy of pre-operative digital templating in total hip arthroplasty performed in a low-volume, resource-constrained orthopaedic unit

Abstract: Aims: Total hip arthroplasty (THA) is considered one of the most successful surgical procedures in modern medicine. The success of THA is well documented, and includes high patient satisfaction rates, low morbidity rates and cost-effective surgery. Most publications come from THA performed in high-volume arthroplasty units, done in high-income countries. Limited data is available on THA performed in low-volume, low-income countries. The aim of this study was to evaluate the accuracy of digital templating in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…The presented study showed a tendency to predicting the acetabular component too large (30% planned too large, 19% too small), which coincides with the results reported by Wiese et al, where a tendency to estimate both components too large was proven [29].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The presented study showed a tendency to predicting the acetabular component too large (30% planned too large, 19% too small), which coincides with the results reported by Wiese et al, where a tendency to estimate both components too large was proven [29].…”
Section: Discussionsupporting
confidence: 92%
“…However, it may be questioned whether ± two implant sizes should still be taken as accurate. Wiese et al showed a planning accuracy of 71% for the acetabular and 79% for the femoral component [ 29 ]. Roughly, the results of the current investigation match those of the studies mentioned above (Table 3 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our accuracy rates were low compared to those recorded in earlier investigations (Table 4 ). The reasons for low templating accuracy in our dataset may have been due to human error in the templating process, as reported by Wiese et al [ 30 ]. Additionally, Carter et al, Bertram The et al, and Choi et al have reported that surgeon experience has a significant role in the accuracy of predicting component size during templating [ 7 , 14 , 31 ].…”
Section: Discussionmentioning
confidence: 74%
“…Prior research regarding digital reference sizers has described the use of a coin piece and spherical ball bearing to decrease magnification discrepancies in plain films, with the most accurate marker being the spherical ball bearing [14][15][16][23][24][25][26][27][28]. Studies involving a coin as the reference marker demonstrated that this method lacks reproducibility, likely due to the variation in size of the coin from rotational positioning in the radiograph [7,16,17].…”
Section: Discussionmentioning
confidence: 99%